How Does the Labor Protection Law Affect Sustainable Economic Growth: An Empirical Analysis Based on Psychological Contract Perspective - Liao, Yina (Frontiers in Psychology, 2022)
This article studied the influence of labor Contract Law and employee psychological contract on enterprise investment and sustainable economic growth. The results indicate that the labor Protection Law has no significant influence on the investment of state-owned enterprises. In the early stage of the implementation of labor Protection Law, the Labor protection Law will observably reduce the investment level of private enterprises, and this effect is more obvious in labor-intensive industries and small and medium-sized enterprises. However, in the later stage of the implementation of Labor Protection Law, the impact of Labor protection Law on the investment of private listed companies is weak. The results indicate that the Labor protection Law increases the illegal costs of private enterprises, reduces the flexibility of employment, and ultimately reduces the investment level of enterprises. Moreover, our article examines the impact of the Labor protection Law on regional economic growth, and finds that the Labor protection Law will significantly reduce the regional GDP growth rate in China, and this effect is mainly reflected in the regions where private enterprises provide more jobs and the proportion of private economy is high. This paper takes China's emerging markets as the background, on the one hand, expands the relevant research on labor market friction from the viewpoint of enterprise investment and economic growth, on the other hand, provides new evidence for state-owned enterprises to fulfill social goals.